SISTEM INFORMASI BERORIENTASI OBJEK DENGAN PEMODELAN UNIFIED MODELING LANGUAGE PADA JASA SECURITY PT. PUTRATAMA KARYA MANDIRI - Mari Rahmawati (Jurnal Sistem Informasi, 2014)
Abstract—In a corporate environment the computer is an absolute tool used for the implementation of computerbased information systems become an absolute necessity and can provide a competitive advantage, so it gets high priorities. With the Unified Modeling Language (UML) to support the description and design of software systems, especially systems that are built using object-oriented programming. To achieve progress in terms of services and facilitate the work, it is necessary to repair, especially in companies engaged in services as one of the security services. Start of the process of securing approval of a proposal by the company's service users, Recruitment security (security), selection, training, job placement company security personnel to service users through the reporting process.